Racism and sexual oppression in Anglo-America : a genealogy - McWhorter, Ladelle, 1960- (Indiana University Press, 2009)
Does the black struggle for civil rights make common cause with the movement to foster queer community, protest anti-queer violence or discrimination, and demand respect for the rights and sensibilities of queer people? Confronting this emotionally charged question, Ladelle McWhorter reveals how a carefully structured campaign against abnormality in the late 19th and early 20th centuries encouraged white Americans to purge society of so-called biological contaminants, people who were poor, disabled, black.